Efektivitas Relaksasi Meditasi Dan Dzikir Terhadap Kecemasan Sebelum Menghadapi Ujian Nasional Pada Siswa Di MTS Tanwiriyyah Cianjur Tahun 2022 - Citra Fitri Firotika; Nurul Ainul Shifa; Saiful Gunardi (Lembaga Pengembangan Kinerja Dosen, 2023)
Introduction: Anxiety is a physiological state that has an impact on heart rate increasing rapidly, in this condition occurs when a person is under stress which makes him uneasy, every individual who experiences anxiety becomes one of the psychological problems that arise. Anxiety itself often appears but with unclear circumstances. To overcome anxiety can be done relaxation meditation and dhikr. Purpose: This research is to find out about the effectiveness of relaxation meditation and dhikr on students' anxiety before facing national exams. Methods: In this study using a pre-experimental type with a research design of two groups pre test - post test design with questionnaire sheets. The sample used was 20 people using purposive sampling. Results: Based on the results of statistical tests the results obtained were p-value = 0,002 for meditation relaxation and p-value <,001 for dhikr. Seen there is effectiveness or a significant effect on students' anxiety before and after meditation and dhikr relaxation. Which means H0 is rejected and Ha is accepted. Conclusion: Based on the results of research conducted that there is effectiveness between meditation and dhikr relaxation on students' anxiety before facing national exams.